2022
DOI: 10.3400/avd.ra.22-00035
|View full text |Cite
|
Sign up to set email alerts
|

Current Clinical Implications of Frailty and Sarcopenia in Vascular Surgery: A Comprehensive Review of the Literature and Consideration of Perioperative Management

Abstract: Frailty is a well-known geriatric syndrome of impaired physiological reserve and increased vulnerability to stressors. Sarcopenia is also used as a parameter of physical impairment characterized by muscle weakness. As population aging has become more prominent in recent years, both modalities are now regarded as clinically important prognostic tools defined by multidimensional factors that may affect clinical outcomes in various clinical settings. A preoperative surgical risk analysis is mandatory to predict c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Frailty, characterised by an increased vulnerability to adverse health outcomes and commonly associated with ageing, is now increasingly recognised as a significant factor in peri‐operative risk assessment. Adjusting risk evaluation based on frailty assessment using a validated screening tool among patients aged 70 years or older in addition to functional capability measures, such as self‐reported ability to climb two flights of stairs, carries an ESC/ESA class IIa, level B recommendation 8,28,29 …”
Section: Pre‐operative Cardiovascular Risk Assessmentmentioning
confidence: 99%
“…Frailty, characterised by an increased vulnerability to adverse health outcomes and commonly associated with ageing, is now increasingly recognised as a significant factor in peri‐operative risk assessment. Adjusting risk evaluation based on frailty assessment using a validated screening tool among patients aged 70 years or older in addition to functional capability measures, such as self‐reported ability to climb two flights of stairs, carries an ESC/ESA class IIa, level B recommendation 8,28,29 …”
Section: Pre‐operative Cardiovascular Risk Assessmentmentioning
confidence: 99%
“…Sarcopenia has been defined by the European Working Group on Sarcopenia in Older People as a syndrome characterized by progressive and generalized loss of skeletal muscle mass and strength with a risk of adverse outcomes 4 . Studies conducted in various other surgical populations have demonstrated that sarcopenia is associated with greater rates of postoperative complications, intensive care unit admittance, increased duration of hospital stay and overall increased economic burden 5–9 . Therefore, illustrating the importance of quantifying a patient's muscle mass and diagnosing sarcopenia preoperatively.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Studies conducted in various other surgical populations have demonstrated that sarcopenia is associated with greater rates of postoperative complications, intensive care unit admittance, increased duration of hospital stay and overall increased economic burden. 5 , 6 , 7 , 8 , 9 Therefore, illustrating the importance of quantifying a patient's muscle mass and diagnosing sarcopenia preoperatively. Recent studies have shown that computed tomography (CT) scan analysis is a valid and reliable tool for determining the presence and severity of sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…In the last consensus published by the European Working Group on Sarcopenia in Older People (EWGSOP), it was recommended to measure muscle strength by handgrip using dynamometry and muscle mass mainly by dual-energy X-ray absorptiometry or bioimpedance analysis [ 3 ]. However, this condition is still overlooked in clinical practice, and despite a common effort toward the identification of parameters able to predict clinical and surgical outcomes [ 4 ], a simple and valid method to identify sarcopenia in clinical settings is needed. In particular, the assessment of frailty and sarcopenia may be a useful prognostic tool to predict perioperative clinical and surgical outcomes and may be an important part of the preoperative decision-making process for surgical strategies.…”
Section: Introductionmentioning
confidence: 99%